Metrik Ergonomi Untuk Produk Perangkat Lunak Permainan Pada Aspek Kenyamanan - Arif Susanto; Daniel Oranova Siahaan (Informatics Engineering Department-UWKS, 2015)
It is inevitable that humans have a limited ability to interact with a product or technology that is made. Limitations on the human body is the reason the importance of ergonomic aspects need to be implemented in the design of a product. In the field of information technology, research-related metric ergonomics of a product has been focused on hardware products, such as mouse, monitor and keyboard. This study builds a metric measurement of ergonomic comfort aspect to the game software products. This study primarily consists of several steps. First, an analysis of ergonomic aspects in comfort. Second, these aspects are mapped into the attributes that exist in software quality models like McCall, Boehm and ISO 9126/25010. Third, the preparation of ergonomics metrics based on an analysis of the test results in previous stages. Attributes that are considered relevant as a reference for the testing of the game software. Game software predetermined expert / expert tested the user directly to the start of the installation process until the stage play of the game software. From the analysis of the proposed ergonomics testing metrics, generated 11 software attributes offline games based desktop that can characterize whether a software-based desktop offline games comfortable or not.